Studi Karakter Morfologi dan Fisiologi Varietas Padi Toleran Terhadap Cekaman Kekeringan Pada Sistem Sawah - Maisura, Maisura; Chozin, M A; Lubis, Iskandar; Junaidi, Ahmad; Ehara, Hiroshi (Agrium, 2017)
Water stress is one of factors which causes low yield of lowland. This study aimed to identify and characterize morphology and physiology of drought tolerant rice varieties. Experiments which have conducted: (i) Investigation of rice varieties tolerance to drought stress at early vegetative stage in the laboratory (ii) morphology and physiology characters of rice varieties to drought stress in the paddy field and (iii) determining the character of root of  rice tolerant to drought stress. The experimental design used was split plot design with 3 (three) replications, with drought stress as the main plot and the variety as sub-plot. The result of screening test at the laboratory using PEG (Polyethylene Glycol) which could characterize which rice varieties could be considered as drought tolerant varieties. Results showed that periods of drought increasing the proline content at Ciherang (25.38 μmol) and IPB 3S varieties (22.08 μmol) at 13 WAT (Week After Transplanting). The variety that has the highest total sugar content in the flowering stage is Rokan (289.38 mg.g-1DW) followed by Menthik Wangi (230.53 mg.g1DW), while the lowest sugar content in harvest found in Jatiluhur (17.14 mg.g-1DW) followed by Way Apo Buru (46.99 mg.g-1DW). Jatiluhur, Way Apo Buru and IPB 3S varieties have drought tolerant based on the root characteristic. Ciherang, IPB 3S, Way Apo Buru and Jatiluhur varieties were drought tolerant and potential to be used in paddy field.